Herbarium Media: Enhancing Science Learning Outcomes for Grade 4 Students on Leaf Bone Shape: Media Herbarium: Meningkatkan Hasil Pembelajaran Sains Siswa Kelas 4 pada Materi Bentuk Tulang Daun di Sekolah Dasar - M Yuslam Abadillah; Enik Setyawati (Universitas Muhammadiyah Sidoarjo, 2023)
This study aimed to investigate the effectiveness of utilizing herbarium media in improving science learning outcomes for fourth-grade students. The research employed a quantitative approach, specifically a pre-experimental design with a one-group pretest-posttest design method. The independent variable (X) was the experimental method using herbarium media, while the dependent variable (Y) was student learning outcomes. The study was conducted at SDN Gelam 1, with a sample size of 25 students (14 males and 11 females) from class IV. Data analysis was performed using a t-test. The results indicated that the use of dried plant herbarium media significantly influenced the learning outcomes of the students, with a significant value of 0.048 (<0.05). Consequently, the null hypothesis (H0) was rejected, and the alternative hypothesis (H1) was accepted. The application of herbarium media demonstrated an 83.8% improvement in the cognitive learning outcomes of fourth-grade students, as it facilitated a better understanding of the subject matter. These findings suggest that employing the herbarium media experimental method can effectively enhance science learning outcomes for fourth-grade students at Gelam 1 Elementary School. Highlights: Herbarium media improves science learning: The use of herbarium media enhances the science learning outcomes of grade 4 students, providing a valuable resource for studying leaf bone shapes and connecting it to the surrounding environment. Experimental approach and design: The study employs a quantitative experimental approach Significance of learning media: Limited learning media can hinder student absorption in learning. The research highlights the importance of utilizing effective learning resources, such as herbarium media, to enhance student engagement and understanding in science education. Keywords: Herbarium media, science learning outcomes, grade 4 students, elementary schools, leaf bone shape